The murder of police officers - Kaminski, Robert J., 1953- (Criminal justice (LFB Scholarly Publishing LLC), 2004)
This study advances research on violence against the police by incorporating both structural covariates and routine work activity factors in a model of police homicide victimization. Based on criminal opportunity theory, it is hypothesized that differences in levels of exposure to motivated offenders and officer physical and social guardianship across 190 municipal law enforcement agencies in four time periods influence opportunities for murders of police, once the effects of criminogenic structural conditions of the jurisdictions in which agencies are located have been taken into account (i.e., proximity to motivated offenders). Given the generally inconsistent results obtained in previous research, particular attention is paid to statistical modeling issues, such as collinearity among regressors, clustering, and the rare-event count nature of the dependent variable.